Unlocking the Success of MSMEs in Digital Era: Shopee Digital Literacy Training, Form SDGs Number 8 - Rahmawati, Apriana; Yanto, Alif Faruqi Febri; Firdaus, Mohammad Iqbal (Edumedia Solution, 2024)
The aim is for MSMEs to understand the role of digital literacy on the Shopee platform. Providing this education is a form of Shopee's support for Sustainable Development Goals (SDGs) number 8, namely